The use of synthetic speech in language learning tools: review and a case study (2010)
This Chapter aims to bring up a discussion on the use of Computer Synthesized Speech (CSS) in the development of Computer-Aided Speech and Language Therapy (CASLT) tools for the improvement of the communication skills in handicapped individuals. CSS is strongly required in these tools for two reasons: Providing alternative communication to users with different impairments and reinforcing the correct pronunciation of words and sentences. Different possibilities have arisen for this goal, including pre-recorded audio, embedded Text-to-Speech (TTS) devices or talking faces. These possibilities are reviewed and the implications of their use with handicapped individuals are commented, showing the experience of the authors in the development of tools for Spanish speech therapy. Finally, a preliminary study in the use of computer-based tools for the teaching of Spanish to young children showed how the synthetic speech feature in the language learning tool was sufficient to maintain the possibilities of the tool as a valuable language teaching element in the absence of other visual elements.